2015
DOI: 10.3892/or.2015.4285
|View full text |Cite
|
Sign up to set email alerts
|

Frizzled2 mediates the migration and invasion of human oral squamous cell carcinoma cells through the regulation of the signal transducer and activator of transcription-3 signaling pathway

Abstract: Frizzled2 (Fzd2) is a receptor for wingless-type MMTV integration site family members (Wnts), the aberrant overexpression of which has been noted to contribute to cancer metastasis. The present study was performed to characterize the role of Fzd2 in the migration and invasion of oral squamous cell carcinomas (OSCC) in vitro. Using TSCCa cells (a tongue SCC cell line) for loss- or gain-of-function of Fzd2, we found that a forced overexpression of Fzd2 promoted TSCCa cell migration and invasion, decreased the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…Exposing EC cells to β-catenin stabilization antagonist XAV939 did affect Fzd2-mediated cell migration, further suggesting the dependence on the canonical Wnt pathway. However, previous studies have shown that Wnt5-Fzd2 activates both β-catenin-dependent (canonical) and β-catenin-independent (noncanonical) signaling (25)(26)(27). Moreover, at some stage of tumor progression, a switch appears to arise between β-catenin-dependent and β-catenin-independent signaling, consistent with the finding that XAV939 could not fully reverse the Fzd2-mediated cell migration.…”
Section: Discussionsupporting
confidence: 85%
“…Exposing EC cells to β-catenin stabilization antagonist XAV939 did affect Fzd2-mediated cell migration, further suggesting the dependence on the canonical Wnt pathway. However, previous studies have shown that Wnt5-Fzd2 activates both β-catenin-dependent (canonical) and β-catenin-independent (noncanonical) signaling (25)(26)(27). Moreover, at some stage of tumor progression, a switch appears to arise between β-catenin-dependent and β-catenin-independent signaling, consistent with the finding that XAV939 could not fully reverse the Fzd2-mediated cell migration.…”
Section: Discussionsupporting
confidence: 85%
“…These receptors orchestrate growth and migration of HNSCC in response to diverse autocrine or paracrine signal ligands in tumors (19,23,35). We also identified other cell signaling receptors such as ITGA6, SERPINE1, and FZD2, which have been implicated in proliferation, adhesion, migration, and differentiation of HNSCC both in vitro and in vivo (17,24,36,37).…”
Section: Discussionmentioning
confidence: 84%
“…They concluded that Fzd2 mediates the migration and invasion of OSCC cells at least partly by regulating the STAT3 signaling pathway. They suggest that Fzd2 could be a novel therapeutic target of OSCC …”
Section: Discussionmentioning
confidence: 99%
“…They suggest that Fzd2 could be a novel therapeutic target of OSCC. 23 Frizzled2 (Fzd2) is a receptor for wingless-type MMTV integration site family members (Wnts), the aberrant overexpression of which has been noted to contribute to cancer metastasis. Wnt5a-Fzd2 pathway may be involved in OSCC metastasis.…”
Section: Discussionmentioning
confidence: 99%